2021
DOI: 10.3389/fgene.2021.633564
|View full text |Cite
|
Sign up to set email alerts
|

Weaning Induces Stress-Dependent DNA Methylation and Transcriptional Changes in Piglet PBMCs

Abstract: Changes to the epigenome, including those to DNA methylation, have been proposed as mechanisms by which stress can induce long-term physiological changes in livestock species. Pig weaning is associated with dietary and social stress, both of which elicit an immune response and changes to the hypothalamic–pituitary–adrenal (HPA) axis. While differential methylation following stress has been assessed in model organisms, it remains poorly understood how the pig methylome is altered by stressors in production sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Many such studies have identified strong associations between cell-specific lowly methylated regions (cLMRs) and TF binding motifs as well as GWAS SNPs for relevant traits, highlighting the potential significance of these regions and of DNA methylation in regulating gene and phenotype expression [22][23][24][25][26]. DNA methylation patterns have previously been characterized in mixed porcine immune cell preparations [17,27]. However, assessment of methylation patterns in specific porcine immune cell types has not been performed, but could provide insight into transcriptional regulation and hence function relevant to pig health.…”
Section: Introductionmentioning
confidence: 99%
“…Many such studies have identified strong associations between cell-specific lowly methylated regions (cLMRs) and TF binding motifs as well as GWAS SNPs for relevant traits, highlighting the potential significance of these regions and of DNA methylation in regulating gene and phenotype expression [22][23][24][25][26]. DNA methylation patterns have previously been characterized in mixed porcine immune cell preparations [17,27]. However, assessment of methylation patterns in specific porcine immune cell types has not been performed, but could provide insight into transcriptional regulation and hence function relevant to pig health.…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of NR3C1 expression, as observed after weaning in piglets fed skimmed cow milk, has been noted in animals that experienced early life stress (142) and in humans diagnosed with posttraumatic stress disorder (PTSD) (143,144). However, this result contradicts the findings of studies on weanling piglets (54), that reported downregulation of NR3C1 expression in contrast to high levels of circulating cortisol.…”
Section: Discussionmentioning
confidence: 94%
“…Modulation of the immune system has lifelong consequences and may be studied through molecular biology assays, which are tools to explore gene expression levels and regulation methods (51). Recently, studies have focused on the abundance of mRNAs from peripheral blood mononuclear cells (PBMCs) (52) isolated from immune cells in whole blood (53), to assess gene expression changes in response to adverse stimuli associated with stressful events (54,55).…”
Section: Introductionmentioning
confidence: 99%
“…There are therefore heritable alterations in gene expression that do not necessitate any change in the DNA sequence ( Jirtle and Skinner, 2007 ; Guerrero-Bosagna and Skinner, 2012 ). Epigenetic processes influence the ability of an organism to adjust to prevailing environmental perturbance and include DNA methylation, histone acetylation, and non-coding ribonucleic acids ( Ju et al, 2020 ; Corbett et al, 2021 ). These modifications are classical epigenetic mechanisms involved in packaging the chromatin structure, regulating DNA damage, and repressing gene expression, among other transcriptional activities ( Bannister and Kouzarides, 2011 ; Hunt et al, 2013 ).…”
Section: Gene-antioxidant Modulation and Hydrocarbon Tolerancementioning
confidence: 99%